Badania jakościowe wobec postulatu teoretyczności wiedzy - Malewski, Mieczysław (Krytyka metodologiczna w praktyce tworzenia wiedzy, 2019)
An explosion of qualitative research in social sciences is accompanied by doubts as to its theorizing potential. Some voices claim that this type of research is “from the nature” idiographic. The main thesis of this study is that change in the way of seeing scientific theory began in the 1960s, with the move from the sociocentric perspective to the anthropocentric perspective. This had important methodological consequences. The prevailing perspective of methodological holism began to be replaced by methodological individualism. As a result, social researchers abandoned the product theory that had been in force to that point. The concept of process theory took its place.